Determination of Sulphide in Arabian Seawater using UV- Visible Spectrophotometer - Butt, N. Z.; Mohsin, F. (The Nucleus, 2022)
High concentration of sulphide in cooling water being utilized for condenser tubes cause stress cracking corrosion, microbially induced corrosion and pitting corrosion phenomenon. Fouling of condenser tube by sulphide is highly undesirable because it reduces the heat transfer capabilities, increases backpressure in the condenser thus affecting the turbine performance. In this work, a method was established for determination of sulphide ion in Arabian sea water using Ultraviolet-Visible Spectroscopy technique. The experiments conducted show precise values for sample (seawater) as well as for absorbencies of standard solutions. Maximum absorbance of methylene blue complex has determined after scanning the equipment from 400 to 700 nm and was found around at 600 nm. Two different sampling points (Machli Chowk & a Conventional Power Plant) were selected to get the average concentration of sulphide in Arabian Sea. The average sulphide concentration in Machli Chowk sample was found out to be 0.287Â±0.031 ppm and average sulphide concentration near a conventional power plant was found out to be 0.31Â±0.029 ppm. Average sulphide concentration was also compared with the Sindh Environmental Quality Standards (SEQS) to validate the results which recommends less than 1 ppm for sulphide concentration in seawater.